Advanced approaches to engineering education - Aleshkevich Николай Александрович; Sviridova Валентина Владимировна; Semchenko Алина Валентиновна; Aleshkevich О.А. (Chrezvychaynye situatsii: obrazovanie i nauka, 2008)
The paper considers the modern requirements on the level and content of engineering education and some aspects of the tuition of skilled and required specialists. The authors emphasize the necessity of transforming the content of general and special subjects, introducing the modem education technologies and means for their implementation, expanding contacts of educational institutions with industry, and improving of information providing of the tutorial process.